Distributed event-triggered algorithm for optimal resource allocation of second-order multi-agent systems - Deng, Zhenhua; Wang, Lei (IET control theory & applications, 2020)
In this work, the authors study the resource allocation problems of second-order multi-agent systems, where each agent is associated with a local cost function and the decisions of agents are constrained by network resource constraints. To seek the optimal resource allocation with low communication costs, a distributed algorithm with event-triggered schemes is proposed. With the help of Lyapunov stability theory and convex analysis, the authors analyse the convergence of the algorithm and prove the event-triggered schemes are free of Zeno behaviour. Under the proposed algorithm, the second-order agents exponentially converge to the exact optimal decision of the resource allocation problem, and the burden of communication is reduced effectively. Finally, a simulation of the economic dispatch problem is given to illustrate the effectiveness of the authors' results.